2018
DOI: 10.1002/hyp.13132
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and analytical studies of solute transport during run‐off over vegetated surfaces

Abstract: Solute transport in overland flow is considered as one of the main contributors to water pollution. Although many models of pollutant transport mechanism from soil to run-off water have been proposed, the characteristics of solute transport accompanying the water run-off over vegetated surface have not been well studied. In this study, a series of laboratory experiments were conducted to study the solute transport over vegetated surfaces. Based on the experimental results, an idea of the "stationary water laye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…According to previous studies, the concept of a ‘thin layer’, which was called the mixing layer, exchange layer, active layer, stationary water layer or control layer in various studies, is widely recommended for describing the solute transport in overland flows, regardless of the area type (Ahuja et al, 1981; Deng et al, 2005; Gao et al, 2004, 2005; Zhang et al, 2018; Zhang, Xiao, Liang, Tang, Xu, et al, 2020). The so‐called mixing layer, exchange layer and active layer are located above the soil surface and are part of the soil layer, which determines how much chemical is available for extraction by the overlying flow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, the concept of a ‘thin layer’, which was called the mixing layer, exchange layer, active layer, stationary water layer or control layer in various studies, is widely recommended for describing the solute transport in overland flows, regardless of the area type (Ahuja et al, 1981; Deng et al, 2005; Gao et al, 2004, 2005; Zhang et al, 2018; Zhang, Xiao, Liang, Tang, Xu, et al, 2020). The so‐called mixing layer, exchange layer and active layer are located above the soil surface and are part of the soil layer, which determines how much chemical is available for extraction by the overlying flow.…”
Section: Discussionmentioning
confidence: 99%
“…Transport rates per unit area with various H C and n values theory can be extended to other area types, such as the soil slopes and the vegetated areas. Zhang et al (2018) indicated that the control layer theory, which was called the stationary water layer in their study, is applicable to the impervious vegetated surfaces. It should be noted that the depth of the control layer is an order of magnitude smaller than that of the mixing layer or exchange layer according to previous studies (Ahuja et al, 1981;Dong et al, 2013;Gao et al, 2004Gao et al, , 2005Yu et al, 2013;Zhang et al, 1997;Zhang, Xiao, Liang, Tang, Xu, et al, 2020), unless the area surface roughness is very large, as for the vegetated surface (Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies (Deng et al, 2005;Xiao et al, 2017;Zhang et al, 2018), sodium chloride (table salt) has been chosen as the dissolved pollutant tracer in this study. Therefore, in this study, we assume that the table salt dissolves over a short period of time T r .…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that the properties of the buildings and impervious catchments are the same, all the surfaces were treated in the same way. Similar to previous studies (Deng et al, 2005;Xiao et al, 2017;Zhang et al, 2018), table salt (NaCl) has been chosen as the dissolved pollutant tracer due to its wide availability and ease of use. In the BH method, buildings are excluded from the computational domain, whereas, the rainwater falling on top of the buildings is compensated by increasing the imposed rainfall intensity over the computational domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation